Femicidio, tutela judicial efectiva y derechos humanos en mujeres víctimas de violencia - Jiménez Ordoñez, Mariuxi Paulina (2023)
The project addresses the problem of femicide, an extreme form of gender violence directed against women because of their gender. The proposed objective is to carry out an analytical study and contrast femicide from the perspective of human rights, especially effective judicial protection. The methodology is inductive-deductive, analytical-synthetic, it includes a conceptual, descriptive and cross-sectional review, with a mixed approach, qualitative by the critical review of doctrine, jurisprudence and Ecuadorian law and quantitative by the statistical analysis of the information, as well as the analysis of the causes and manifestations of this phenomenon. The main results of the research indicate that femicide is a responsibility for the State and society, and judicial protection as a signifier should guarantee the prevention, protection, investigation, prosecution and punishment of those responsible, as well as comprehensive reparation for the victims and their families. In conclusion, femicide is a complex and multifaceted phenomenon that requires a joint commitment with the State to eradicate it. It is necessary to recognize and protect the specific human rights of women, especially in situations of violence, in order to guarantee a life free of violence and discrimination.